Comparison Between Acute Leukemia Screening Tube and Lineage-Specific Panels for the Diagnosis of Acute Leukemia in Kenya - Douglas I. Munga; Nancy A. Okinda; Geoffrey A. Omuse; Elizabeth M. Kagotho (JCO Global Oncology)
PURPOSEAcute leukemia is a group of hematologic malignancies categorized according to the immature cells that proliferate and replace the normal bone marrow. Flow cytometry has emerged as a cornerstone in the diagnosis of hematologic malignancies. Staged analysis with a screening tube containing specific lineage markers determines the need for subsequent testing if there is an abnormal population (blasts). The specific lineage panels to be analyzed are determined depending on the positive markers in the screening tube. This study aimed to determine the agreement of diagnosis using the acute leukemia screening tube (ALST) and the lineage-specific panel.METHODSThis was an analytical cross-sectional study performed at the Aga Khan University Hospital, Nairobi. It included 256 cases diagnosed as acute leukemia. The diagnosis after the screening tube was compared with the final diagnosis from the lineage-specific panels, and Cohen's Kappa was used to determine the level of agreement.RESULTSOf the 256 cases, the overall agreement was 94%, with 14 cases being discordant. Myeloperoxidase interpretation in the screening tube accounted for 64% (9 of 14) of the discrepant results.CONCLUSIONThe study demonstrated that the ALST is almost as good as lineage-specific panels in the diagnosis and classification of acute leukemias. The screening tube can be an added diagnostic tool to complement morphology in resource-limited centers with the capacity to interpret flow cytometry analysis.